2018
DOI: 10.1002/chem.201704079
|View full text |Cite
|
Sign up to set email alerts
|

A Self‐Repairing Cathode Material for Lithium–Selenium Batteries: Se−C Chemically Bonded Selenium–Graphene Composite

Abstract: Lithium–selenium batteries, employing selenium as a cathode material, exhibit some notable advantages, such as high discharge rates and good cycling performance, due to their high electrical conductivity, high output voltages, and high volumetric capacity density. However, an important problem, termed the “shuttle effect”, can lead to capacity decay in Li‐Se cells (and in Li‐S cells), which arises from aggregation and the loss of Se or S from the cathode into the electrolyte. In this work, in order to solve th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 43 publications
(41 reference statements)
2
34
0
Order By: Relevance
“…As for C 1s spectra of cycled MiC/Se cathode (Figure 6c,d), the relative intensity of the peak at 290.2 eV that corresponds to CSe bond is obviously increased, indicating that the interaction between Se atoms in chain‐like Se x molecules and C atoms in sp 2 framework of MiC substrate become stronger after one cycle. [ 23,45,46 ] Consistent with the C 1s spectra, an additional peak at 57.8 eV can be seen in Se 3d spectra due to the aforementioned CSe bond (Figure 6e). However, the C‐Se interaction in cycled MeC/Se cathode is greatly weaker than that of cycled MiC/Se cathode.…”
Section: Resultssupporting
confidence: 69%
“…As for C 1s spectra of cycled MiC/Se cathode (Figure 6c,d), the relative intensity of the peak at 290.2 eV that corresponds to CSe bond is obviously increased, indicating that the interaction between Se atoms in chain‐like Se x molecules and C atoms in sp 2 framework of MiC substrate become stronger after one cycle. [ 23,45,46 ] Consistent with the C 1s spectra, an additional peak at 57.8 eV can be seen in Se 3d spectra due to the aforementioned CSe bond (Figure 6e). However, the C‐Se interaction in cycled MeC/Se cathode is greatly weaker than that of cycled MiC/Se cathode.…”
Section: Resultssupporting
confidence: 69%
“…[ 33 ] Therefore, it can be concluded that the C−N heteroatomic coordination of PANi with the Se/C particles facilitates Li 2 Se n anchoring, and thus, a reversible electrochemical reaction between Se and Li, leading to enhanced capacity retention. [ 10 ]…”
Section: Resultsmentioning
confidence: 99%
“…Recently, lithium–selenium (Li–Se) batteries have been considered one of the promising next‐generation batteries not only because they offer a high energy density (2528 Wh L −1 ), which is higher than that of graphite–LiFePO 4 and comparable to that of Li–S batteries, but also because the active material, Se, has a higher electrical conductivity compared with S and LiFePO 4 (10 −3 S m −1 of Se vs 10 −28 S m −1 of S and 10 −7 S m −1 of LiFePO 4 ). [ 5,7,10–26 ] Therefore, a higher utilization of Se in LiBs provides a higher energy density in spite of the lower amount of conductive carbon. [ 12,20–22 ] Moreover, the compatibility of Se with low‐cost carbonate‐based electrolytes reduces costs and mitigates capacity decay, unlike in Li–S batteries where the nucleophilic reaction of carbonyl groups with S degrades the cell performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a low-temperature alloying method, ball-milling is highly efficient in preparing the alloys and composites [41][42][43][44][45][46]. As for the graphene based heterogeneous electrode materials, ball milling exhibited the advantages in the size/ layer reduction [47], interface-contact enhancement [48,49] as well as the low cost and time saving [50].…”
Section: Strategies For the Assembly 21 Ball-millingmentioning
confidence: 99%